Efficiency of Nitrogen Fertilization in Shallots (Allium ascalonicum,.L) with the Addition of Cow Manure - MUHAMMAD JUWANDA, MUHAMMAD JUWANDA (Talenta Publisher, 2023)
This research was conducted to determine the effect of nitrogen fertilizer and cow manure on the growth, yield, and efficiency of shallot plant growth. This research was conducted in the rice fields of Brebes, Brebes Regency. This study is a factorial experiment using a randomized block design (RAK) with two factors. The first factor is the application of nitrogen fertilizer 1/3 N (Urea) + 2/3 N (ZA) which consists of 4 levels, namely 0 N kg/ha (N0); 100 N kg/ha (N1); 200 N kg/ha (N2) and 300 N kg/ha (N3). The second factor is the application of organic material of cow manure with 4 levels, namely 0 t/ha (K0); 10 t/ha (K1); 20 t/ha (K2) and 30 t/ha (K3). There were 16 treatments, each treatment was repeated three times. plant height, number of leaves, leaf area (g), number of tillers per plant, number of tubers per plant, fresh weight of plant per clump (g), weight of tuber per clump (g), dry weight of plant per clump (g), weight of tuber dry per clump (g), tuber volume per clump (mL), N uptake (g), fertilization efficiency N (%). Observational data were analyzed with the F test to determine the diversity and if there was a significant difference, proceed with DMRT with an error rate of 5%. The results showed that the administration of a nitrogen dose of 200 kg N/ha was able to increase the growth and yield of shallots compared to other treatments. The best efficiency of N fertilization was in the application of 100 kg N/ha nitrogen fertilizer.